Sertifikat Elsimil sebagai Persyaratan Nikah dalam Upaya Pencegahan Stunting Perspektif Maqāṣid al-Syarī‘ah: Studi di KUA Kecamatan Kisaran Barat - Malau, Mashuri Lot; Hasanah, Uswatun (Borneo : Journal of Islamic Studies, 2025)
Marriage marks the beginning of family formation, which requires physical, mental, emotional, and financial readiness, particularly in facing health risks such as stunting. To address this issue, the government, through Presidential Regulation No. 72 of 2021 in collaboration with BKKBN, launched the Electronic Ready for Marriage and Pregnancy Certificate (Elsimil) as a premarital health screening instrument. This study aims to analyze the implementation of the Elsimil Certificate as a marriage requirement in preventing stunting at the Office of Religious Affairs (KUA) of Kisaran Barat District from the perspective of Maqāṣid al-Syarī‘ah, as well as to assess its effectiveness as a public policy based on maṣlaḥah (public interest). The research employed a qualitative method with a combined normative and empirical approach. Data were collected through interviews, observations, and documentation. The results show that the implementation of Elsimil at the KUA of Kisaran Barat District has been relatively effective in reducing stunting rates, as indicated by a significant decline in cases following its implementation. Conceptually, this policy aligns with the objectives of Maqāṣid al-Syarī‘ah in achieving public welfare through the protection of life (ḥifẓ al-nafs) and lineage (ḥifẓ al-naṣl), and serves as evidence of the integration of Islamic values into modern public policy focused on family health.